2013
DOI: 10.19154/njwls.v3i2.2547
|View full text |Cite
|
Sign up to set email alerts
|

Working in the Public Sector Introduction to the Thematic Issue

Abstract: ork in the public sector has been changing dramatically in recent decades. Reforms aimed at increasing the efficiency of public services have been extensive in the Nordic countries and elsewhere since the 1980s. The reforms and changes have to a large extent been associated with so-called New Public Management (NPM) principles, emphasizing the market as a central coordination mechanism. Consequently, public institutions have been restructured, their services are standardized and commodified, and market-like re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Workplace deregulation with a focus on task continuity in accordance with increased emphasis on techno-economic rationality requires that a temporary change of workplace is unproblematic for employees. This kind of regulation has been enabled by the market adjustment that elderly care has undergone in the Nordic countries since the 1980s, which has entailed an increased emphasis on tasks performed within strict time limits (Kamp et al, 2013;Szebehely & Meagher, 2013;Trygdegård, 2012). Emphasis on techno-economic rationality clashes with care rationality (Waerness, 1996), in which relationship continuity is a prerequisite for care work.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace deregulation with a focus on task continuity in accordance with increased emphasis on techno-economic rationality requires that a temporary change of workplace is unproblematic for employees. This kind of regulation has been enabled by the market adjustment that elderly care has undergone in the Nordic countries since the 1980s, which has entailed an increased emphasis on tasks performed within strict time limits (Kamp et al, 2013;Szebehely & Meagher, 2013;Trygdegård, 2012). Emphasis on techno-economic rationality clashes with care rationality (Waerness, 1996), in which relationship continuity is a prerequisite for care work.…”
Section: Discussionmentioning
confidence: 99%
“…Reforms and changes have to a large extent been in accordance with the principles of New Public Management (NPM) (Kamp et al, 2013a). With many management practices drawn from the private sector, outsourcing and privatization were common.…”
Section: Changing Contextmentioning
confidence: 99%
“…In the public sector, most work is service work, largely done by women (Kamp et al, 2013a; Swedish Agency for Public Management, 2015) and bearing in mind the high rates of absenteeism due to illness and longterm sick leave in the public sector (Vingård et al, 2005;Lund et al, 2008;Sverke et al, 2016), it is of interest to study how OHS providers are utilized in the public sector. This is particularly of importance since it has been shown that the prevalence of long-term work ability is higher in municipalities where there is a well-structured OHSM (Dellve et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A sector dominated by women that is interesting to look closer at in relation to this question is health care. From an overall perspective there has been a privatization trend in Swedish health care, with instability and changes to the ownership structures as a consequence, which has erased the borderlines between public and private sectors and affected the work conditions (Kamp et al 2013). On top of this economic recession and the associated demand for efficient, streamlined organizations have led to a constantly increasing pace of working, and in its pursuit of efficiency, the sector has turned to the manufacturing industry's established management concepts such as Lean production (Brännmark and Holden 2012, McCann et al 2015, Sederblad 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Well known is that groups on the work market that have low-status positions, as many women in health care have, are more often than those who have high-status positions negatively affected by organizational changes . Consequently many women in the Swedish health care industry are exposed to negative changes in their working conditions due to privatization and/or new public management (NPM) strategies such as Lean thinking (Kamp et al 2013). In the late 1990s Landsbergis et al (1999) published an article on what impact Lean has on workers' health, and have also presented health issues such as stress and musculoskeletal diseases (MSDs).…”
Section: Introductionmentioning
confidence: 99%